2008
DOI: 10.1002/pola.22626
|View full text |Cite
|
Sign up to set email alerts
|

Negative‐type photosensitive poly(phenylene ether) based on poly(2,6‐dimethyl‐1,4‐phenylene ether), a crosslinker, and a photoacid generator

Abstract: A negative‐type photosensitive poly(phenylene ether) (PSPPE) based on poly(2,6‐dimethyl‐1,4‐phenylene ether) (PPE), a novel crosslinker 4,4′‐methylene‐bis [2,6‐bis(methoxymethyl)phenol] (MBMP) having good compatibility with PPE, and diphenylidonium 9,10‐dimethoxy anthracene‐2‐sulfonate (DIAS) as a photoacid generator (PAG) has been developed. This resist consisting of PPE (73 wt %), MBMP (20 wt %) and DIAS (7 wt %) showed a high sensitivity (D0.5) of 58 mJ/cm2 and a contrast (γ0.5) of 9.5 when it was exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…In contrast, additive‐free PAA film reaches 80% of imidization at 250 °C. The cleavage percentage of DNCDP with exposure to 500 mJ/cm 2 was around 17%, estimated by data in the previous report of photosensitive poly(benzoxazole) using PBG 30. It is indicated that low‐temperature imidization of this PSPI completed in the presence of a small amount of DMP.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…In contrast, additive‐free PAA film reaches 80% of imidization at 250 °C. The cleavage percentage of DNCDP with exposure to 500 mJ/cm 2 was around 17%, estimated by data in the previous report of photosensitive poly(benzoxazole) using PBG 30. It is indicated that low‐temperature imidization of this PSPI completed in the presence of a small amount of DMP.…”
Section: Resultsmentioning
confidence: 51%
“…In contrast, additive-free PAA film reaches 80% of imidization at 250 C. The cleavage percentage of DNCDP with exposure to 500 mJ/cm 2 was around 17%, estimated by data in the previous report of photosensitive poly(benzoxazole) using PBG. 30 It is indicated that low-temperature imidization of this PSPI completed in the presence of a small amount of DMP. In a previous work, the PAA film from BPDA and ODA containing a base catalyst could enforce imidization at 200 C. 25 This PSPI film, however, required high thermal treatment at 250 C to complete the imidization.…”
Section: Figurementioning
confidence: 93%
“…In this study, we prepared a crosslinked poly(2,6‐DMP(95 mol %)‐ co −2,6‐DPP(5 mol %)) in two steps; poly(2,6‐DMP 95 ‐ co −2,6‐DPP 5 ) was prepared by the oxidative coupling polymerization using a toluene/water heterogeneous system, followed by the reaction of the poly(2,6‐DMP 95 ‐ co −2,6‐DPP 5 ) with 4,4′‐methylenebis[2,6‐ bis (methoxymethyl)] phenol (MBMP) as the crosslinking agent. The MBMP has been used with aromatic polymers and provides the desired balance of flexibility, exterior durability, chemical resistance, and film toughness . The crosslinked poly(2,6‐DMP 95 ‐ co −2,6‐DPP 5 ) had the excellent ε′ of 2.6 and tan δ of 0.004 at 10 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that sulfonic acids generated in the exposure area catalyze the formation of benzylic carbocation species, which undergo the electrophilic substitution on the thiophene rings and the self-condensation of cross-linkers to produce cross-linked polymers. These reactions convert soluble P3HT films into insoluble films in chloroform as shown in Scheme 1 [5].…”
Section: Patterning Processmentioning
confidence: 99%